Model Integrating Fuzzy Argument with Neural Network Enhancing the Performance of Active Queue Management - Kim Quoc, Nguyen; Thanh Tu, Vo; Thuc Hai, Nguyen (EAI Endorsed Transactions on Context-aware Systems and Applications, 2015)
The bottleneck control by active queue management mechanisms at network nodes is essential. In recent years, some researchers have used fuzzy argument to improve the active queue management mechanisms to enhance the network performance. However, the projects using the fuzzy controller depend heavily on professionals and their parameters cannot be updated according to changes in the network, so the effectiveness of this mechanism is not high. Therefore, we propose a model combining the fuzzy controller with neural network (FNN) to overcome the limitations above. Results of the training of the neural networks will find the optimal parameters for the adaptive fuzzy controller well to changes of the network. This improves the operational efficiency of the active queue management mechanisms at network nodes.